2017
DOI: 10.1111/iju.13330
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor‐alpha inhibits differentiation of myogenic cells in human urethral rhabdosphincter

Abstract: Tumor necrosis factor-α inhibits differentiation of urethral rhabdosphincter cells in part through the p38 mitogen-activated protein kinase and phosphoinositide 3-kinase pathways. Inhibition of tumor necrosis factor-α might be a useful strategy to treat stress urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Enrichment analysis of the KEGG pathway reveals involvement in various pathways, including tumor, inflammation, and endocrine systems. Shinohara et al [50] found that TNF-α has an inhibitory effect on urethral smooth muscle cells, suggesting that inhibiting TNF-α may have some effect on potential treatments for urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment analysis of the KEGG pathway reveals involvement in various pathways, including tumor, inflammation, and endocrine systems. Shinohara et al [50] found that TNF-α has an inhibitory effect on urethral smooth muscle cells, suggesting that inhibiting TNF-α may have some effect on potential treatments for urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the impact of inflammation on UI. Shinohara et al demonstrated that TNF-α suppressed the myogenic differentiation of human urethral rhabdosphincter cells, suggesting that TNF-α may be a risk factor of SUI in the elderly [ 24 ]. Additionally, inflammation also plays a role in overactive bladder (OAB) associated with UI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TNF-α was shown to inhibit the myogenic differentiation of human RS progenitor cells through the PI3K and p38-mitogen activated protein-kinase (MAPK) pathways in a dose-dependent manner. Based on this, the research group established an immortalized human RS cell line to identify a possible new therapy for SUI through autologous transplantation of muscle or adipose-derived stem cells ( Shinohara et al, 2017 ).…”
Section: Muscle-derived Factorsmentioning
confidence: 99%